(untitled) (Global Journal of Science Frontier Research, 2018)
A cross-sectional study was conducted to estimate the prevalence and economic importance of fasciolosis slaughtered at Wulnchit Municipal Abattoir from November, 2011 and April, 2012. A total of 500 livers from cattle selected were examined with systematic random sampling for the presence of liver fluke. Of 500 examined cattle, 171 (34.23%) livers were infected with Fasciola. Both species of Fasciola were identified during the study. These are Fasciola hepatica (F. hepatica) and Fasciola gigantica (F. gigantica). From 171 livers F. hepatica were 120 (70.17%), F. gigantica 30 (17.54%) livers, while mixed infection with both was 11 (6.4 %) animals and 10 (5.8%) cattle were infected with unidentified immature liver flukes. F. hepatica was found to be the predominant fasciola species causing bovine fasciolsis in the study areas. Statistically significant variation was observed in the prevalence of fasciolosis among animals with medium (50%) and good (32.9%) body conditions (P